Let us now calculate the cutting length of 6-legged stirrups as shown below.

**Cutting length formula for stirrup-1**

= [(2nos × a1) + (2nos. × b1) + (2nos. × hook length) - {(3nos. × 90° bend )+ (2nos. × 135° bend)}]

First, we will calculate the value of a1 & b1

a1 = [(column width ) - {(2nos. × clear cover) + (2nos.× 1/2 dia. of stirrup-1 bar)}]

= [ ( 750mm ) - { ( 2nos. × 40mm ) + ( 2nos. × 1/2 × 8mm )}]

= [ 750mm - { 80mm + 8mm }]

= [ 750mm - 88mm ]

= 662mm.

b1 = [ x + ( 2nos.× 1/2 dia. of mid bar.) + ( 2nos. × 1/2 dia of stirrup-1 bar )]

x = [column depth -{(2nos.×cover )+( 2nos.× dia. of stirrup-3)+ (2nos.× 1/2 dia. of outer bar)}] ÷ 3

= [ 600mm - {( 2nos. × 40mm ) + ( 2nos. × 8mm ) + ( 2nos.× 1/2 × 20mm )}] ÷ 3

b1 = [ x + ( 2nos.× 1/2 dia. of mid bar.) + ( 2nos. × 1/2 dia of stirrup-1 bar )]

= [ 161.33mm + ( 2nos. × 1/2 × 16mm ) + ( 2nos. × 1/2 × 8mm )]

= [ 161.33mm + 16mm + 8mm]

= **185.33mm.**

**The cutting length for stirrup-1**

= [(2nos × a1) + (2nos. × b1) + (2nos. × hook length) - {(3nos. × 90° bend )+ (2nos. × 135° bend)}]

= [ (2nos.× 662mm) + ( 2nos. × 185.33mm ) + (2nos. × 10d ) - {( 3nos.× 2d ) + ( 2nos. × 3d )}]

**Note**:

1. Here,10d is taken for hook length.

2. We have deducted 2d for 90° bend -3nos., & 3d for 135° bend -2nos. as similar to the above drawing in all the 3 types of stirrups.

=[ 1324mm + 370.66mm + ( 2nos. × 10 × 8mm ) - {( 3nos.× 2× 8mm) + ( 2nos. × 3 × 8mm)}]

= [1694.66mm + 160mm - { 48mm + 48mm }]

= [1854.66mm - 96mm ]

= **1758.66mm.**

#### 2. Stirrup-2:

**Cutting length formula for stirrup-2**

= [(2nos × b2) + (2nos. × a2) + (2nos. × hook length) - { (3nos. × 90° bend )+ (2nos. × 135° bend)}]

First, we will calculate the value of b2 & a2

b2 = [(column depth ) - {(2nos. × clear cover) + (2nos.× 1/2 dia. of stirrup-2)}]

= [ ( 600mm ) - { ( 2nos. × 40mm ) + ( 2nos. × 1/2 × 8mm )}]

= [ 600mm - { 80mm + 8mm }]

= [ 600mm - 88mm ]

=** 512mm.**

a2 = [ y + ( 2nos.× 1/2 dia. of mid bar.) + ( 2nos. × 1/2 dia of stirrup-2 )]

First, we will find out the value of y

y = [column width -{(2nos.×cover )+( 2nos.× dia. of stirrup-3)+ (2nos.× 1/2 dia. of outer bar)}] ÷ 3

= [ 750mm - {( 2nos. × 40mm ) + ( 2nos. × 8mm ) + ( 2nos.× 1/2 × 20mm )}] ÷ 3

= [ 750mm - { 80mm + 16mm + 20mm }] ÷ 3

= [ 750mm - 116mm ] ÷ 3

= 634mm ÷ 3

y = 211.33mm.

a2 = [ y + ( 2nos.× 1/2 dia. of mid bar.) + ( 2nos. × 1/2 dia of stirrup-2 )]

= [ 211.33mm + ( 2nos. × 1/2 × 16mm ) + ( 2nos. × 1/2 × 8mm )]

= [ 211.33mm + 16mm + 8mm]

= **235.33mm.**

**The cutting length for stirrup-2**

= [(2nos × a2) + (2nos. × b2) + (2nos. × hook length) - {(3nos. × 90° bend )+ (2nos. × 135° bend)}]

= [ (2nos.× 235.33mm) + ( 2nos. × 512mm ) + (2nos. × 10d ) - {( 3nos.× 2d ) + ( 2nos. × 3d )}]

=[ 470.66mm + 1024mm + ( 2nos. × 10 × 8mm ) - {( 3nos.× 2× 8mm) + ( 2nos. × 3 × 8mm)}]

= [1494.66mm + 160mm - { 48mm + 48mm }]

= [1654.66mm - 96mm ]

= **1558.66mm.**

**3. Stirrup-3**

**Cutting length formula for stirrup-3**= [(2nos.× a3) + (2nos. × b3) + (2nos. × hook length) - {(3nos. × 90° bend )+ (2nos. × 135° bend)}]

First, we will calculate the value of a3 & b3

a3 = [(column width ) - {(2nos. × clear cover) + (2nos.× 1/2 dia. of stirrup-3)}]

= [ ( 750mm ) - { ( 2nos. × 40mm ) + ( 2nos. × 1/2 × 8mm )}]

= [ 750mm - { 80mm + 8mm }]

= [ 750mm - 88mm ]

=** 662mm.**

b3 = [(column depth ) - {(2nos. × clear cover) + (2nos.× 1/2 dia. of stirrup-3)}]

= [ ( 600mm ) - { ( 2nos. × 40mm ) + ( 2nos. × 1/2 × 8mm )}]

= [ 600mm - { 80mm + 8mm }]

= [ 600mm - 88mm ]

=** 512mm.**

**The Cutting length of stirrup-3**

= [(2nos.× a3) + (2nos. × b3) + (2nos. × hook length) - {(3nos. × 90° bend )+ (2nos. × 135° bend)}]

= [ (2nos.× 662mm) + ( 2nos. × 512mm ) + (2nos. × 10d ) - {( 3nos.× 2d ) + ( 2nos. × 3d )}]

=[ 1324mm + 1024mm + ( 2nos. × 10 × 8mm ) - {( 3nos.× 2× 8mm) + ( 2nos. × 3 × 8mm)}]

= [2348mm + 160mm - { 48mm + 48mm }]

= [2508mm - 96mm ]

=** 2412mm.**

**For you ðŸ‘‡**

❤How to calculate the cutting length of 4-legged stirrups?

❤How to calculate the cutting length of a circular stirrup?